PdCu nanoparticles modified free-standing reduced graphene oxide framework as a highly efficient catalyst for direct borohydride-hydrogen peroxide fuel cell. (December 2022) - Yin, Xianzhi; Hou, Meiling; Zhu, Kai; Ye, Ke; Yan, Jun; Cao, Dianxue; Zhang, Dongming; Yao, Jiaxin; Wang, Guiling
Abstract: A novel electrode of PdCu nanoparticles modified free-standing reduced graphene oxide (rGO) framework (PdCu@rGOF) is fabricated via electrodeposition and chemical reduction and employed to the direct sodium borohydride-hydrogen peroxide fuel cell (DBHPFC). The resultant catalyst reveals excellent catalytic performance towards hydrogen peroxide (H2 O2 ) electroreduction reaction (HPRR) and sodium borohydride (NaBH4 ) electrooxidation reaction (BOR) along with low activation energy ( E a ). Numerically, the PdCu@rGOF electrode delivers an HPRR current density of 455.2 mA cm −2 at 0 V (2 mol L −1 H2 SO4 +1.3 mol L −1 H2 O2 ). Additionally, the current density of BOR reaches up to 1065.3 mA cm −2 at 0 V for 2 mol L −1 NaOH and 0.3 mol L −1 NaBH4 . Meanwhile, the mechanism studies show that HPRR and BOR catalyzed by PdCu@rGOF mainly relates 2-electron-transfer process and quasi-8-electron-transfer process, respectively. Subsequently, PdCu@rGOF is assembled into a fuel cell, yielding the optimal power density of 188.9 mW cm −2 . The open circuit potential (OCP) of DBHPFC is about 1.70 V at 293.15 K. The superior electrochemical performance of the optimized electrode can be attributed to the distinctive architecture and the strong adsorption and bond-breaking ability of Pd nanoparticles. This work indicates that the as-prepared PdCu@rGOF can be a promising catalyst for DBHPFC. Graphical abstract: Image 1 Highlights: A novel 3D through-hole rGOF framework has been successfully prepared. PdCu@rGOF displays an excellent catalytic performance for HPRR and BOR. PdCu@rGOF can be applied to both anode and cathode of DBHPFC. DBHPFC presents high power density and operation stability.